Harnessing secondary metabolites of endophytic microbes: a next-generation biopesticide for crop disease management - Parveen, Gulafsha; Ansari, Waquar Akhter; Kumar, Navin; Jaiswal, Durgesh Kumar (Frontiers in Microbiology, 2026)
This review highlights the potential of endophytic microorganisms and their secondary metabolites as innovative biopesticides for sustainable disease management in agriculture. Agriculture faces substantial challenges from phytopathogens, resulting in significant economic losses worldwide, which are typically addressed with synthetic pesticides that pose environmental and health hazards. Endophytic microorganisms residing within plant tissues without inducing disease provide a natural defence alternative by synthesising a variety of beneficial secondary metabolites, including alkaloids, terpenoids, phenolics, and peptides. These chemicals serve as ecological mediators, directly inhibiting pathogens, promoting plant systemic resistance, and improving nutrient absorption and stress resilience. The review elucidates the biosynthesis routes of these metabolites, their ecological functions, and the symbiotic chemical interactions between endophytes and host plants that enhance plant growth and defence. Bacterial endophytes, including Bacillus and Pseudomonas, generate lipopeptides that compromise pathogen membranes and to improve plant immunity, whereas fungal endophytes, such as Trichoderma and Penicillium, produce antifungal and insecticidal agents. The manuscript additionally examines the molecular mechanisms that govern these relationships, encompassing phytohormonal signalling and quorum sensing. While the potential of endophytic microorganisms as biopesticides is promising, significant gaps remain in our understanding of their long-term ecosystem effects, molecular mechanisms, and scalable manufacturing techniques. This review highlights the importance of comprehensive research to fully harness the biotechnological potential of endophytes. Integrating their secondary metabolites into crop protection strategies could reduce our reliance on chemical pesticides, promoting environmental sustainability and food security. Understanding the long-term ecosystem effects of endophytic microorganisms is crucial for bolstering resilient agricultural systems globally.